In the Pursuit of (Ald)Imine Surrogates for the Direct Asymmetric Synthesis of Non-Proteinogenic α-Amino Acids - Roche, Stéphane P. (Synthesis, 2021)
Nature remarkably employs posttranslational modifications of the 20 canonical α-amino acids to devise a far larger structural, conformational, and functional diversity found in non-proteinogenic amino acids (NPAAs), which ultimately translates into a plethora of complex biological functions. Synthetic chemists are continuously trying to reproduce and even extrapolate the repertoire of NPAA building blocks to build structural diversity into bioactive molecules and materials. The direct asymmetric functionalization of α-imino esters represents one of the most robust and attractive routes to NPAAs. This review summarizes the most prominent examples of bench-stable (ald)imine surrogates exploited for the synthesis of NPAAs, including our most recent results in the nucleophilic substitution of α-haloglycines and other α-haloaminals. A synopsis of kinetic studies, reaction optimizations, and enantioselective catalytic methods is also presented.1 Introduction2 Asymmetric Synthesis of Tertiary α-Substituted NPAAs2.1 From N,O-Acetals (α-Hydroxy/Alkyloxy/Acetoxyglycines)2.2 From α-Amido Sulfones2.3 From α-Haloglycine Esters2.4 From N,O-Bis(Boc) Hydroxyglycine3 Asymmetric Synthesis of Acyclic Quaternary α,α-Disubstituted NPAAs4 Concluding Remarks
Keywords: (ald)imine surrogates; non-proteinogenic α-amino acids (NPAAs); asymmetric catalysis; H-bond donor catalysts